Proyecto de factibilidad para la creación de una empresa comercializadora de productos ferreteros y materiales pétreos, ubicada en Guamaní al Sur de Quito, Provincia de Pichincha - Jami Hidalgo, Nancy Marlene (2012)
The present research is aimed at creating a marketer of hardware products PÉTREOS MATERIALS AND LOCATED IN SOUTH OF QUITO Guamaní province PICHINCHA whose main objective is to introduce a new concept in the sale of construction products in the market through good corporate governance, with the best quality in order to reach its highest level ma sales, reaching excellent coverage within the country.